Item analysis: basic concepts of physics students in geometric optics - Godelfridus Hadung Lamanepa; Rosenti Pasaribu; Claudia M.M. Maing (Universitas Sultan Ageng Tirtayasa, 2020)
The purpose of this study was to analyze students' items and abilities—the analysis for mapping test instruments and students' basic concepts regarding optics subjects before lectures are held. The test participants were 35 physics students. The analysis model of item response theory is a one-parameter logistic model or Rasch Model with the scope of analysis of the level of item difficulty, student ability, and statements that fit the item response model. Analysis of item responses and student responses carried out using Winstep version 3.73 software. The results of the qualitative analysis of the test items consisted of memory (C1) analysis (C4). The quantitative analysis using the Rasch model showed that 35% of the total items were difficult category items. For the suitability of test items in the instrument by 85% of items fit or generally function in measurement, more than 57% of students have the geometric optical ability in logit values of 0 to 1. The results of item analysis and student ability become information for teachers to design courses such as method selection, project implementation strategies, and assessments are undertaken.